Political Representation and Emotions: The Case of Out Self-Identified LGB Representatives in Canada. Issue 2 (3rd April 2019) - Tremblay, Manon
ABSTRACT: This paper examines the role that out LGBTQ politicians think that emotions have played in their mandate of political representation, using Canada as a case study. My argument is that out LGBTQ politicians employ emotional narratives that constitute meanings to link the personal and the political in a co-constitutive manner: on the one hand, the personal is a source of politicization; on the other hand, politics provides a place where LGBTQ subjectivities can be expressed.